2008
DOI: 10.4103/0022-3859.43523
|View full text |Cite
|
Sign up to set email alerts
|

Nicolau syndrome following intramuscular benzathine penicillin

Abstract: Nicolau syndrome (NS) is a rare complication of an intramuscular injection characterized by severe pain, skin discoloration, and varying levels of tissue necrosis. The case outcomes vary from atrophic ulcers and severe pain to sepsis and limb amputation. We describe a case of a seven-year-old boy with diagnosis of NS after intramuscular benzathine penicillin injection to the ventrolateral aspect of the left thigh. Characteristic violaceous discoloration of skin and immediate injection site pain identified it a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
54
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 6 publications
0
54
0
1
Order By: Relevance
“…It is well described in dermatologic literature as a rare side effect characterized by livedoid dermatitis [3][4][5]7] which occurs after the intra-muscular injection of insoluble substances [4,[7][8][9] Nevertheless, the emergence of the Syndrome is associated with the route of administration and the new pharmaceutical formula of the drug, rather than with its pharmacodynamic properties, and consequently, there is not a specific group responsible for the complication potential. A systematic review showed that predisposing factors, such as watery micro-suspension in the vehicle, in opposition to oily, suggesting a prevalent genesis of the Syndrome's embolism [10] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well described in dermatologic literature as a rare side effect characterized by livedoid dermatitis [3][4][5]7] which occurs after the intra-muscular injection of insoluble substances [4,[7][8][9] Nevertheless, the emergence of the Syndrome is associated with the route of administration and the new pharmaceutical formula of the drug, rather than with its pharmacodynamic properties, and consequently, there is not a specific group responsible for the complication potential. A systematic review showed that predisposing factors, such as watery micro-suspension in the vehicle, in opposition to oily, suggesting a prevalent genesis of the Syndrome's embolism [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Nicolau Syndrome, or Embolia Cutis Medicamentosa, was first described by Juliusberg, Freudenthal and Nicolau between 1924 and 1928 [3][4][5][6]. The first descriptions refer to patients undergoing treatment for syphilis who received injections of bismuth salts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4,5,6 The first descriptions refer to patients under treatment of syphilis that were given injections of bismuth salts. 4,5 It is well described in the dermatological literature as a rare adverse reaction characterized by dermatitis livedoid 3,4,5,7 that occurs after intramuscular injection of insoluble substances.…”
Section: Discussionmentioning
confidence: 99%
“…Nas últimas décadas, foram identificados muitos outros acidentes idênticos, aumentando também o número de casos relatados em publicações médicas e congressos [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] .…”
unclassified